Molecular Characteristics of Brucella Isolates Collected From Humans in Hainan Province, China - Li, Zhenjun; Wang, Xu-ming; Zhu, Xiong; Wang, Miao; Cheng, Hai; Li, Dan; Liu, Zhi Guo (Frontiers in Microbiology, 2020)
Brucellosis has been reported in several regions of Hainan Province, but the extent of the disease has not been fully elucidated. Conventional biotyping methods, multiple locus variable number tandem repeats analysis (MLVA) and single nucleotide polymorphisms (SNPs) from draft genome sequencing were employed to characterize the strains. There were four boivars (B. melitensis bv. 1, 2, and 3 and B. suis bv. 3) detected, which showed that the biovar diversity of Brucella in Hainan is higher than in other areas of China. Both B. melitensis bv. 3 and B. suis bv. 3 were dominant species and showed epidemiology patterns that were compatible with both southern and northern China. Eight of MLVA-11genotypes were known (31, 111, 116, 120, 136, 291, 297, and 345), and the remaining seven were novel (HN11-1 ~ 7); these data showed that Brucella strains in this study had multiple geographic origins and exhibited characteristics of origin and evolution of co-existing imported and Hainan specific lineage. A total of 41 strains were found, belonging to 37 unique genotypes that each represented a single strain, which suggests that these strains were not directly related epidemiologically and indicates that the epidemic characteristics of human brucellosis in Hainan was dominated by sporadic strains. The high HGDI values were observed in MLVA-8, MLVA-11, and MLVA-16 among two species, suggesting considerable genetic diversity among these species. MST is characterized based on MLVA-16 that was found both throughout China and on a global level and showed that strains of this study had significant genetic differences with strains from many parts of the globe and seemingly represent a unique genetic lineage. Whole-genome SNP analysis showed that four B. melitensis were closely related to strains from China’s northern provinces, and the source of infection was partly of human brucellosis in this province that may have been from these regions. The B. suis were closely related to strains from the United States, and further investigation of the transportation of animals, such as pigs, is needed to elucidate the origins of these strains.